Finnish Forest Sector Economic Outlook 2013-2014. Executive summary. - (:unkn) unknown (Metsäntutkimuslaitos, 2013)
The executive summary is a translation of the summary of the Finnish original publication, and is based on information available in early October.
Translation: Semantix Technical editing: Sari Elomaa